Peran Kepuasan Pelanggan sebagai Mediasi Pengaruh Promosi Penjualan, Pengalaman Pelanggan dan Kualitas Sistem terhadap Loyalitas Pengguna Shopee - Wati, Nike Karlina; Fiona, Febzi (Jambura Economic Education Journal, 2026)
This study aims to examine whether customer satisfaction can mediate the influence of sales promotions, customer experience, and system quality on customer loyalty. This research uses a quantitative approach involving a sample of 264 respondents. The research sample was selected based on specific criteria, namely a minimum silver member level, to obtain more representative data from loyal customers. This research also uses an online questionnaire and applies the SEM-PLS 4.0 data analysis model. The results of this study found that there is a significant influence of sales promotions, customer experience, and system quality on customer satisfaction. Furthermore, customer satisfaction can significantly mediate the influence of sales promotions, customer experience, and system quality on loyalty.